2019
DOI: 10.1002/hyp.13388
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence for identifying hydrologically homogeneous regions: A state‐of‐the‐art regional flood frequency analysis

Abstract: Due to the severity related to extreme flood events, recent efforts have focused on the development of reliable methods for design flood estimation. Historical streamflow series correspond to the most reliable information source for such estimation; however, they have temporal and spatial limitations that may be minimized by means of regional flood frequency analysis (RFFA). Several studies have emphasized that the identification of hydrologically homogeneous regions is the most important and challenging step … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Through the analysis of the data of college students' ideological and mental health support services in the results in Figure 7 , it can be found that, under the star continuous analysis model of fuzzy cluster analysis algorithm, the data error degree of the experimental group and the control group will show strong disturbing characteristics with the internal correlation, and its internal data coupling error strategy will also have low-level discrete driving representation. Therefore, the accuracy of the result correlation is very high, while the deviation of the result correlation of the control group is very obvious [ 26 ]. Then we can know that, in the process of practical application, we need to combine the deviation of active participation of different types of college students' ideological and mental health support services to realize its quantitative evaluation and reliability disposal.…”
Section: Results Analysis and Discussionmentioning
confidence: 99%
“…Through the analysis of the data of college students' ideological and mental health support services in the results in Figure 7 , it can be found that, under the star continuous analysis model of fuzzy cluster analysis algorithm, the data error degree of the experimental group and the control group will show strong disturbing characteristics with the internal correlation, and its internal data coupling error strategy will also have low-level discrete driving representation. Therefore, the accuracy of the result correlation is very high, while the deviation of the result correlation of the control group is very obvious [ 26 ]. Then we can know that, in the process of practical application, we need to combine the deviation of active participation of different types of college students' ideological and mental health support services to realize its quantitative evaluation and reliability disposal.…”
Section: Results Analysis and Discussionmentioning
confidence: 99%
“…Furthermore, each of the regionalization approaches (ROI, CCA, CA) considered in this study has several variants. One could attempt preparing ensembles corresponding to different variants of ROI (e.g., Cunderlik & Burn, 2006; Durocher et al., 2018; Formetta et al., 2018; Mostofi & Burn, 2019; Zrinji & Burn, 1996), CCA (e.g., Han et al., 2020; Ouali et al., 2016; Ouarda et al., 2000; Ribeiro‐Corréa et al., 1995; Shu & Ouarda, 2007), and CA (e.g., Basu & Srinivas, 2014, 2016; Cassalho et al., 2019; Farsadnia et al., 2014; Rao & Srinivas, 2006a; Wazneh et al., 2015) for investigating improvement in regions derived by application of FEC to those individual ensembles and their possible combinations.…”
Section: Discussionmentioning
confidence: 99%
“…where d ij represents the distance between any two sample points i and j in the data space, and the formula is as follows [15]:…”
Section: Smart Finance and Accounting Managementmentioning
confidence: 99%